WEEKLY PHYSICAL ACTIVITY OF TABLE TENNIS PLAYERS - Branko Đukić; Branislav Strajnić; Vladimir Ivanek (Sport Scientific And Practical Aspects, 2025)
Everyone who practice sports shows a developed awareness of the importance of physical exercise by developing their performance in sports training and diet, which together certainly contribute to the sports result, and above all to the improvement and preservation of health. The aim of this work is to determine the way of conducting physical activities of athletes who play table tennis on a weekly basis, as well as to establish whether there are differences between the categories of physical activities between men and women. The research includes a total of 40 respondents, of which 18 are male table tennis players and 22 are female table tennis players who play for clubs participating in the First League of Serbia in the 2023/24 competition season. By comparing the level of physical activity of table tennis players, it was concluded that there is no statistically significant difference in physical activity expressed in MET values on a weekly basis between male table tennis players and female table tennis players, as well as in daily sitting next to small screens, at work or with friends